Échelle spectroscopy of the chemically peculiar star θ1 Ori F. Issue 3 (27th August 2021) - Costero, Rafael; Allen, Christine; Ruelas-Mayorga, Alex; Sánchez, Leonardo; Ramírez Vélez, Julio; Echevarría, Juan; Melgoza, Gustavo C
ABSTRACT: We analyse Échelle spectra of θ 1  Ori F obtained by us on six nights unevenly distributed along 6 yr; we identify several hundred spectral lines and measure, for the first time, the star's heliocentric radial velocity. We also collect and discuss previously published photometry of θ 1  Ori F. We find that θ 1  Ori F is a chemically peculiar (CP) star with overabundant silicon and phosphorus, and possibly other elements as well. From the singly ionized Fe, Cr and Ti lines we estimate its spectral type to be between B7 and B8. The radial velocity of θ 1  Ori F is possibly marginally variable, with an average of 24 ± 4.2 km s −1  (standard deviation), in good agreement with the mean radial velocity of the Orion Nebula Cluster members, and about 5 km s −1 smaller than the average of the other Trapezium components. We cast doubt on the coeval nature of this star relative to the other Trapezium components, and present arguments that almost certainly exclude its membership to the Orion Trapezium. θ 1  Ori F turns out to be enigmatic in several respects, and is probably an important link for understanding the evolutionary stage at which the CP phenomenon sets on.